Emaranhado - Rocha, Clara Pitanga; Bombardi, Alice; Rodrigues, Brunno; Lima, Luciana Martins Tavares de (Revista do Colóquio, 2024)
In this visual essay, it’s presented Tangled (2024), a performance-action involving an artistic intervention on Avenida Brigadeiro Faria Lima. This intervention used a spool of string to create a three-dimensional tangle that temporarily reconfigured the space in front of the Google building. The action aimed to briefly transform the predominantly work-oriented environment into a playful space.